Pengaruh Latihan Yoga terhadap Involusi Uterus pada Ibu Nifas - Mu’alimah, Miftakhul; Kartikasari, Dewi; Sunaningsih, Sunaningsih; Puspita Sari Pakpahan, Yunita (Fakultas Ilmu Kesehatan, 2022)
The puerperium period is the period used to restore the obstetric organs as before pregnancy with approximately 6 weeks, and this puerperal period lasts normally until the uterus returns to its original shape. A common puerperal complication is post partum hemorrhage, which is caused by one of them because the involution process is not running well. Puerperal yoga is a form of effort to make the involution process run normally, which aims to facilitate the occurrence of the uterine involution process, strengthening the pelvic floor muscles postpartum. The purpose of this study was to determine the Effect of Yoga Practice on Uterine Involution in Puerperal Mothers in PMB Mrs.